Control of the cattle tick Boophilus microplus with Metarhizium anisopliae, laboratory and field studies. - LÓPEZ, ELKIN; LÓPEZ, GUSTAVO; ORDUZ, SERGIO (Revista Colombiana de Entomología, 2009)
The biocontrol potential of eight strains of Metarhizium anisopliae was evaluated for the cattle tick Boophilus microplus under laboratory and field conditions. The strain 137bm caused the highest effect on the reproductive capacity of the tick, decreasing tick oviposition by 90 and 96% when adult ticks were treated in vitro with 1x108 and 1x109 conidia/ ml. It also reduced egg viability by more than 98% in the same doses. In the field trials it was possible to reduce tick infestation by 75% in Holstein x Cebú cows when M. anisopliae 137bm was applied at a concentration of 1x108 conidias/ ml. Also, the fecundity of the ticks coming from cows treated with M. anisopliae was three times lower than that of the control group. On the other hand, strain 137bm applied to the meadow at a concentration of 5x1012 conidia/ha concentration caused a decrease in the larval tick population close to 86% one week after an application with conidia of M. anisopliae.